Exploring the Agromorphological Profiles of the Cacao (Theobroma cacao L.) Collection from the INIA Germplasm Bank in the Amazonas Region, Peru - Tejada Alvarado, José Jesús (2025)
Cacao represents a crop of strategic importance for Peru due to its socioeconomic value, which has driven initiatives for the collection, characterization, and conservation of its genetic diversity, with a view to the future development of elite plants. As part of these efforts, a collection of 113 accessions was established, with agromorphological data were recorded over two consecutive growing seasons, comprising 33 quantitative and 18 qualitative descriptors. These data were analyzed using univariate and multivariate statistical approaches, as well as Bayesian inference models. The results revealed broad phenotypic diversity, with significant variation in quantitative fruit and seed descriptors (CV = 37.51%), which was accompanied by high heritability values (> 60%) and considerable genetic advance (> 20%). Furthermore, eight phenotypic groups were identified, with Cluster II distinguished by its oblong fruits and higher pod index, and Cluster III by superior seed traits, including a greater number of fully developed seeds per fruit and an outstanding seed index (> 1.3 g). This comprehensive characterization enables the identification of accessions with promising agronomic traits and high bioactive potential, supported by phytochemical analyses using HPLC and FTIR. These findings provide a robust scientific foundation for breeding programs focused on developing more competitive and sustainable cacao production.